Characteristics and Survival of Patients with WHO Grade 4 Diffuse Glioma in Dharmais National Referral Cancer Hospital - Tadjoedin, Hilman; Suryana, Kresna Dharma; Rosalina, Rosalina; Hartono, Bryan Arista; Widarta, Oskar Ady; Dewin, Nikrial; Andriani, Rini (Indonesian Journal of Cancer, 2024)
Background: The WHO grade 4 diffuse glioma are extremely aggressive and account for over 60% of adult Central Nervous System (CNS) tumors. The diagnosis and management pose significant challenges due to the need for comprehensive evaluation and holistic treatment approaches. This study aims to determine the clinical characteristics of WHO grade 4 diffuse glioma in Indonesia and the overall survival as a secondary goal. Methods: This is a retrospective cohort study of all WHO grade 4 glioma patients from 2017 to 2022 at Dharmais National Cancer Hospital, Jakarta, Indonesia. Demographic characteristics were presented descriptively. Kaplan-Meier plot was used to evaluate the median survival. Results: Twenty-eight patients were eligible for this study. The median age group is 45 years old, with equal male and female prevalence. Headache was the most prevalent primary symptom. The therapy following surgery was radiotherapy (RT) with chemosensitizer (82.1%) and RT alone (14.3%) with both followed by adjuvant chemotherapy. There was one patient (3.6%) underwent palliative therapy. The median survival of all patients was 10 months, whereas 10 months in RT with the chemo-sensitizer group and 1 month in RT only group. There was no statistically significant difference between RT with and without chemotherapy sensitizer in terms of survival rates. Conclusions: Our study reports a younger median age of WHO Grade 4 diffuse glioma. Male subjects were equivalent to females. Median OS was 10 months and were longer in RT with the chemosensitizer group. Further multicentered and at the genetic level investigation was needed, to achieve optimal outcomes.